Implementation Of Criminal Actions Against Malpractice By Medical Personnel - Zara Shelli Meirosa (Ius Poenale, 2021)
Providing health services to the community is very important, where every community must get proper health services and according to permission from the government. However, in terms of providing services to the community, things that are not supposed to be done by medical personnel are not uncommon, such as malpractice. Malpractice in the provision of health services by medical personnel is a legal problem that must be addressed immediately. One way is through criminal threats for the perpetrators. In Law Number 36 of 2009 concerning Health, there have been many provisions regarding criminal sanctions for medical personnel who make mistakes in carrying out their health practices. This action must be assessed in terms of criminal law to impose sanctions on perpetrators who have committed malpractice. The research method used in this study uses a normative approach method. Normative research is legal research, carried out by examining library materials or secondary data as the necessary material to be studied by searching for the regulations and literature related to the problem under study. The approach to the problem used is the statutory approach. The results of this study answer that the types of malpractice committed by medical personnel are when in malpractice, in addition to actions that are considered negligence, some actions are included in the category of deliberate action and violating the law, the existence of an act, due to serious injury, the causal relationship between severe injuries and forms of action, the existence of forms of actions and the existence of consequences: wounds that cause disease; and injuries which prevent him from carrying out occupational work, or searching for a specified time. Malpractice that is done intentionally is a form of pure malpractice, including in criminal malpractice. Furthermore, the legal consequence of malpractice committed by medical personnel is the emergence of criminal liability for medical personnel as legal subjects which are closely related to proving someone's actions (medical personnel) to be included in the criminal malpractice category if the act fulfills the formulation of criminal offenses. Therefore, the imposition of criminal sanctions against medical personnel who commit malpractice can be punished. This research suggests that law enforcement officials should take an active role in handling malpractice cases in health services